Literatur Review : Edukasi Penanganan Tersedak pada Anak - Yoany Maria V.B. Aty; Magdalena Kewa Deran (Poltekkes Kemenkes Mataram, 2021)
Choking often occurs in people's lives. To be able to overcome this condition, a person's skills are needed to quickly and accurately provide help, in order to save victims from serious conditions, namely disability or even death. This study aims to collect and analyze the effect of education on the level of knowledge and ability of first aid in children who are choking. This research is a literature study by conducting a review of previous research using some relevant literature. Search for articles using search engines including Google and data bases such as Google Scholar, Research Gate, and PUBMED, with a limitation on the year of publication of articles for the last 10 years, starting from 2011-2020. Articles used in Indonesian and English are downloaded in full text in PDF format and are free articles. Based on the results of the analysis of relevant journals, it was found that education had an effect on the level of first aid ability for children who experienced choking. Simulation/demonstration is an effective method to educate family/community in providing first aid (airway management) for airway obstruction due to choking.